Poor health-related quality of life (hrqol) and fatigue are associated with a higher work productivity impairment in systemic lupus erythematosus (sle) patients - Reategui Sokolova, Cristina (2019)
Background: Because most patients with SLE are in their productive-age years, the ability to maintain a gainful employment is fundamental for both, the patient and society at large. It is thus quite important to determine the work and non-work factors that are associated with work productivity impairment in these patients. Objectives: To determine the factors associated with absenteeism (percentage of the time missed from scheduled work-time over the preceding 7 days, due to SLE), presenteeism (percentage of time from scheduled work-time where productivity was impaired while patient was at work, over the preceding 7 days, due to SLE) and overall work impairment (combination of absenteeism and presenteeism) in patients with SLE.